Adsorption-Desorption Behaviour of Boron in Soils of Assam - Tamuli, Babita; Bhattacharyya, D.; Borua, N.G.; Basumatary, A. (Asian Journal of Chemistry, 2017)
Batch studies were conducted to investigate the adsorption and desorption behaviour of boron in four soils of Assam viz. entisol, inceptisol, alfisol and ultisol, which had wide variations in physico-chemical properties. The adsorption isotherms indicated that the adsorption of boron increased with its increasing concentration in the equilibrium solution. The Langmuir adsorption isotherm was curvilinear and it was significant when the curves were resolved into two linear parts. The maximum value of the adsorption maxima (b1) was observed to be 2.657 μg g-1 in ultisol and the bonding energy (k) constant was maximum at 2.073 mL μg-1 in inceptisol. The Langmuir isotherm best explains the adsorption phenomenon at low concentration of the adsorbent, which was different for different soils. There was significant correlation between b1 and organic carbon (r = 0.916**), clay content (r = 0.739*) and free Al2O3 (r = 0.791*) of the soils. A linear relationship was observed between log C and log x/m in all soils and at the whole concentration range from 0.1 to 10 μg B mL-1 which indicated that B adsorption data also conform to the Freundlich equation. Soils that had higher affinity for B adsorption (S4), tended to desorb less amount of B (37.92 %) and that had lower affinity for B adsorption (S3) showed greater desorption (53.78 %) of adsorbed B. Boron desorption by these soils showed a significant positive correlation with sand content (r = 0.801*) and significant negative correlation with organic carbon (r = –0.709*), CEC (r = –0.834**) and free Al2O3 (r = –0.785*) of the soils. The maximum value of desorption maxima (DmB) (56.497 μg g-1) and B mobility (KdB) (0.061 mL μg-1) was observed in ultisol (S4).